Constructing positive narrative identities in a forensic setting: a single case evaluation of phototherapy. Issue 1 (11th March 2019) - Saita, Emanuela; Accordini, Monica; Loewenthal, Del
Abstract : Purpose: The purpose of this paper is to evaluate the use of a phototherapeutic technique called "Talking Pictures" within the forensic setting. This approach involves the use of a set of photographs to facilitate clients' disclosure, self-growth and promote the development of positive self-narratives. The use of art therapies and the construction of adaptive identity narratives have been proven to support desistance and increase resocialization in the prison population. Design/methodology/approach: A 42-year-old Italian male offender was met for six therapy sessions and invited to talk about his past, present and future through the use of photographs. Session transcripts were analysed using the software for linguistic analysis T-LAB. Findings: Results show a progression in the language used during the sessions: in the beginning the client uses a denotative language with many concrete nouns and no emotional words, in subsequent sessions his speech begins to assume more symbolic connotations and emotional words are used to describe past traumas as well as to find new meanings to present events. Moreover, the fixity of the client's self-image is contrasted with the emergence of new sides to his personality encompassing agency and self-worth. Research limitations/implications: The study is based on a single case, therefore results cannot be generalised to the prison population; moreover, the absence of any follow-up and standardized measurements of the client's progression should be addressed by future research by both involving larger samples and including follow-up and quantitative measures of the study results. Practical implications: The paper provides details on an innovative technique that might be used to explore the offenders' goods and values and to develop truly redemptive rehabilitation programmes. Originality/value: This paper adds to the scant literature on phototherapy in prisons and connects it with a reflection on desistance indicating that phototherapeutic interventions might be used to promote positive self-narratives, thus increasing desistance.